The relationship between workplace design features and job performance - Elhami @ Che Kassim, Kamarudin (2020)
This research seeks to examine the relationship between workplace design features and job performance. Based on a comprehensive literature review, a theoretical model is proposed for investigation. This research is performed through quantitative, and a total of 200 questionnaires are circulated through a google form. The data are collected from one of government agency buildings utilized online data collection. The researcher used a convenience sampling approach and a structured questionnaire. A self administrated structured questionnaire is used to collect data. The result showed that there is positive the relationship between lighting, acoustic and relative humidity. The study confirmed that workplace design is significantly correlated with job performance. The findings of the study indicate that there is a strong positive relationship between workplace design features and job performance.